Analysis of the Situation and Influencing Factors of Fungal Detection in Adult Patients with Severe Diseases in Tibet Region - FU Jianlei (Editorial Office of Medical Journal of Peking Union Medical College Hospital, 2021)
Objective  To explore the situation of fungal detection in adult patients with severe diseases in Tibet region, and further analyze the influencing factors of fungal detection.  Methods  All patients admitted to the Department of Critical Care Medicine Tibet Autonomous Region People's Hospital from January 1, 2018 to December 31, 2019 were retrospectively analyzed. According to the results of fungal detection, the patients were then divided into the positive group and the negative group. The distribution of fungal strains detected and clinical data of the two groups were collected by the electronic medical record system. Multivariate Logistic regression was used to analyze the influencing factors of fungal detection.  Results  A total of 755 severe patients (4917 specimens were submitted) were enrolled, including 142 patients with positive fungal detection and 613 patients with negative fungal detection.Of which, 192 fungal strains were detected, including 183(95.3%) Candida strains, 7(3.7%) Aspergillus strains and 2(1.0%) other fungi strains. Among Candida genus, there were 164 strains (89.6%) of Candida albicans, 9 strains (4.9%) of Candida glabrata, 7 strains (3.8%) of Candida parapsilosis, 2 strains (1.1%) of Candida krusei, and 1 strain (0.6%) of Candida tropicalis. Among Aspergillus, there were 3 strains (42.8%) of Aspergillus fumigatus, 2 strains (28.6%) of Aspergillus niger, and 2 strains (28.6%) of Aspergillus flavus. Multivariate Logistic regression analysis showed that, high sequential organ failure assessment score (OR=1.402, 95% CI: 1.277-1.538, P < 0.001), severe digestive diseases (OR=2.671, 95% CI: 1.465-4.872, P=0.001), the duration of tracheal intubation ≥48 h(OR=2.661, 95% CI: 1.611-4.397, P=0.000), the use of carbapenemes ≥24 h (OR=2.825, 95% CI: 1.522-5.245, P=0.001), the use of cephalosporins plus beta lactamase inhibitor ≥24 h (OR=2.678, 95% CI: 1.679-4.272, P=0.000), and the long ICU stay (OR=1.043, 95% CI: 1.011-1.076, P=0.008) were independent risk factors for fungal detection in adult patients with severe diseases. High altitude of residence (OR=0.999, 95% CI: 0.999-1.000, P=0.040) and the high hemoglobin level (OR=0.994, 95% CI: 0.988-0.999, P=0.020) were protective factors.  Conclusions  Positive fungal detection in adult patients with severe diseases in the Tibet area is not uncommon, and Candida albicans is the main strain detected. The factors affecting the detection of fungi involve many aspects. Corresponding preventive measures should be taken according to the characteristics of Tibet.